TRANSFORMING DENTISTRY: THE RISE OF INTRAORAL SCANNERS – A REVIEW - ELANGOVAN, DR HARIPRASHANNA; SABAPATHY, DR KANNAN; JACULIN B, CHRISHELLE (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Intraoral scanners (IOS) have transformed the landscape of dental impression taking, offering a modern, digital alternative to traditional methods. By utilizing advanced optical imaging technology, these devices capture precise 3D representations of the oral cavity, significantly enhancing patient comfort and procedural efficiency. This review explores the various types of intraoral scanners, their technological underpinnings, and the multitude of benefits they provide, including improved accuracy, reduced treatment times, and streamlined workflows in dental practices. Despite their advantages, challenges such as high initial costs, learning curves, and limitations in certain clinical scenarios remain. This review underscores the importance of embracing these innovations to enhance patient outcomes and practice efficiency.